2014
DOI: 10.1016/j.jtcvs.2013.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia in patients undergoing thoracotomy: Epidural versus paravertebral technique. A randomized, double-blind, prospective study

Abstract: According to our data, drugs administered through a paravertebral catheter are very effective. Moreover, it does not present contraindications to its positioning or collateral effects. More studies are necessary to confirm data we collected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 23 publications
0
24
0
5
Order By: Relevance
“…Carmona et al reported that CPVB analgesia was an acceptable safe technique for early extubation with optimal pain control retrospectively compared with intravenous analgesia with opioids in 37 patients who underwent cardiac surgery [23]. Some authors showed that CPVB was a good pain reliever similar to EA in thoracic surgery [12–15], so we hypothesized that CPVB could potentially replace EA as the standard procedure in open-heart surgery. Although we did not record any pain scales to evaluate the degree of pain, our fentanyl consumption was small compared to past reports [19, 2426], and our patients did not require multiple analgesics as we expected.…”
Section: Discussionmentioning
confidence: 99%
“…Carmona et al reported that CPVB analgesia was an acceptable safe technique for early extubation with optimal pain control retrospectively compared with intravenous analgesia with opioids in 37 patients who underwent cardiac surgery [23]. Some authors showed that CPVB was a good pain reliever similar to EA in thoracic surgery [12–15], so we hypothesized that CPVB could potentially replace EA as the standard procedure in open-heart surgery. Although we did not record any pain scales to evaluate the degree of pain, our fentanyl consumption was small compared to past reports [19, 2426], and our patients did not require multiple analgesics as we expected.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate these side effects, techniques using a catheter, such as continuousslow infusion of local anesthetics into the paravertebral or direct wound space, have recently been established (3)(4)(5). This paravertebral technique, according to Raveglia and colleagues (6), has superior results compared with the PCA methods in thoracotomy patients; however, it has not been fully evaluated with respect to VATS.…”
Section: Original Articlementioning
confidence: 99%
“…El tratamiento adecuado del dolor agudo post-toracotomía facilita la recuperación funcional y disminuye las complicaciones pulmonares y el riesgo de cronificación (síndrome post-toracotomía) (1)(2)(3)(4). En nuestra experiencia, este dolor se controla adecuadamente con un protocolo de analgesia multimodal basado en el bloqueo epidural o paravertebral, asociado a antiinflamatorio no esteroideo (AINE), paracetamol y morfina de rescate, permitiendo una movilización del paciente en las primeras 24 horas.…”
Section: Introductionunclassified